The perception of companies pertaining to the English adequacy of newly employed graduates in Kemaman, Terengganu - a survey among GLC's and private sector / Nor Madihah Mohamed - Mohamed, Nor Madihah (2009)
This survey investigated the perception of two government linked companies and two private sector companies pertaining to the English proficiency of the newly employed graduates. More specifically, the study investigated the work sectors perception of the adequacy o f the listening, speaking, reading, writing and social skills of the newly employed graduates and based on this, the score for the overall English adequacy was computed. The population is the private sector and GLC’s in Kemaman. Stratified sampling was employed and a sample of 115 respondents was selected comprising 45 from GLC’s and 70 from the private sector. The sample comprised those from the supervisory level, executive level and up to the management. There were seven sections in the questionnaire and the individual sections were found to be reliable. Overall, the questionnaire has a high reliability level with a Cronbach’s Alpha of 0.94. An analysis of the descriptive statistics showed that the English skills of the newly employed graduates were not adequate for the working needs pertaining to the following areas; listening, speaking, writing and socializing as the benchmark score of 70% was not achieved. According to the definition in this study, the English proficiency is considered adequate to the working need when a score of at least 70% is achieved. However, the sample indicated that the reading skills of the new graduates are adequate for the working need because the mean score obtained for reading was 72.3%. A t-test indicated that there was no significant difference between the overall English proficiency of the newly employed male and female staff at the workplace. A t-test value of 0.72 was obtained and since it exceeds 0.025, it is clear that there is no significant difference between the overall English proficiency of the newly employed male and female staff.